Safety and efficacy of favipiravir for the management of COVID-19 patients: A preliminary randomized control trial. (July 2022) - Rahman, S.M. Abdur; Kabir, Ahmedul; Abdullah, A.B.M.; Alam, Md Billal; Azad, Khan Abul Kalam; Miah, Md Titu; Mowla, Syed Ghulam Mogni; Deb, Sudip Ranjan; Amin, Mohammad Robed; Asaduzzaman, Muhammad
Highlights: A double-blinded randomized controlled trial for COVID-19 was conducted with antiviral drug Favipiravir. Acceleration of viral clearance and significant improvement in chest X-ray of Pneumonia patient was noted by Favipiravir. Favipiravir did not show notable side effects in COVID-19 patients. Abstract: Background: The novel coronavirus disease, commonly called COVID-19, has already killed millions of lives. Our study aimed to identify a safe and right drug for the management of such globally threatened COVID-19. Methods: This preliminary double-blinded randomized controlled trial was done among 57 hospitalized COVID-19 patients in the early stage of their illness. Of them, 29 patients received Favipiravir (FVP) and the remaining 28 patients received a placebo under the standard of care. Among the patients, 4 from Favipiravir (FVP) group and 3 from the placebo group were discontinued. The patients were observed regularly for a period of 10 days. Result: In our study, the FVP treated group showed accelerated viral clearance compared to the placebo-treated group. Assessment of chest X-ray showed remarkable improvement of pheumonia patient in group A compared to Group B. Hematological and Biochemical parameters such as total WBC count, neutrophil and lymphocyte counts were examined. No significant differences in the hematological parameters such as WBC count, neutrophil and lymphocyte counts in Group A and Group B patients. Liver transaminases levels were also stable in FVP treated group (average ALT ranges 39.4–46.2; AST 28.2–32.8). Conclusion: The drug Favipiravir displayed remarkable improvements in the clinical conditions and recovery of COVID-19 patients at the early stages of their infections.